Health Control Beliefs and Attitude Toward Treatment in Psychiatric and Non-Psychiatric Clinical Samples - Pogany, Laszlo; Lazary, Judit (Frontiers in Psychiatry, 2021)
Although there is accumulating evidence on the potential influencing factors of medication adherence, the knowledge about patients’ attitudes and beliefs towards treatment is only partly utilized in the adherence-improving strategies. Several internal and external factors determining adherence have been described regarding many chronic somatic diseases but in case of psychiatric patients the lack of insight has been almost exclusively in the focus of research. As a result, there is a scarcity of effective adherence-improving interventions. Identification of any specific differences or similarities between the attitudes towards treatment of psychiatric and non-psychiatric patients would help to support adherent behavior. We recruited 189 participants from 4 departments of general psychiatry (GEN PSYCH, n=106), addictology (ADDICT, n=42) and somatic diseases (NON PSYCH, n=41). The Patient’s Health Belief Questionnaire on Psychiatric Treatment (PHBQPT) was performed to assess the patients’ attitude towards drug treatment, perceived health locus of control and psychological reactance. The most robust difference of the PHBQT scores has occurred between the GEN PSYCH and ADDICT subgroups. ADDICT patients scored significantly higher on the internal and external health locus of control and on the Psychological Reactance subscale as well. While GEN PSYCH subjects provided higher score on the Positive Aspect of Medication compared to ADDICT persons. Interestingly, the only difference between the GEN PSYCH and NON PSYCH groups was the more pronounced mistrust in physicians in case of psychiatric patients. Our data suggest that mistrust towards medication does not differ in psychiatric and non-psychiatric samples, while the acceptance of the doctor’s competency may be stronger in the non-psychiatric sample. The analysis of these factors provides information which could help us better understand this important issue and to develop more efficient interventions for improving adherence.